Clinical validation of hrHPV testing on vaginal and urine self-samples in primary cervical screening (cross-sectional results from the Papillomavirus Dumfries and Galloway—PaVDaG study). Issue 4 (25th April 2016) - Stanczuk, Grazyna; Baxter, Gwendoline; Currie, Heather; Lawrence, James; Cuschieri, Kate; Wilson, Allan; Arbyn, Marc
Abstract : Objectives: Papillomavirus Dumfries and Galloway (PaVDaG) assessed the performance of a high-risk human papillomavirus (hrHPV) PCR-based assay to detect high-grade cervical intraepithelial neoplasia (CIN2+) in self-collected vaginal and urine samples. Setting: Women attending routine cervical screening in primary care. Participants: 5318 women aged 20–60 years provided self-collected random urine and vaginal samples for hrHPV testing and a clinician-collected liquid-based cytology (LBC) sample for cytology and hrHPV testing. Interventions: HrHPV testing. All samples were tested for hrHPV using the PCR-based cobas 4800 assay. Colposcopy was offered to women with high-grade or repeated borderline/low-grade cytological abnormalities; also to those who were LBC negative but hrHPV 16/18 positive. Primary and secondary outcome measures: The self-tests' absolute sensitivity and specificity for CIN2+ were assessed on all biospecimens; also, their relative sensitivity and specificity compared with clinician-taken samples. Interlaboratory and intralaboratory performance of the hrHPV assay in self-collected samples was also established. Results: HrHPV prevalence was 14.7%, 16.6% and 11.6% in cervical, vaginal and urine samples, respectively. Sensitivity for detecting CIN2+ was 97.7% (95% to 100%), 94.6% (90.7% to 98.5%) and 63.1% (54.6% to 71.7%) for cervical, vaginal and urine hrHPV detection, respectively. The corresponding specificities were 87.3% (86.4% to 88.2%), 85.4% (84.4% to 86.3%) and 89.8% (89.0% to 90.7%). There was a 38% (24% to 57%) higher HPV detection rate in vaginal self-samples from women over 50 years compared with those ≤29 years. Relative sensitivity and specificity of hrHPV positivity for the detection of CIN2+ in vaginal versus cervical samples were 0.97 (0.94 to 1.00) and 0.98 (0.97 to 0.99); urine versus cervical comparisons were 0.53 (0.42 to 0.67) and 1.03 (1.02 to 1.04). The intralaboratory and interlaboratory agreement for hrHPV positivity in self-samples was high (κ values 0.98 (0.96 to 0.99) and 0.94 (0.92 to 0.97) for vaginal samples and 0.95 (0.93 to 0.98) and 0.90 (0.87 to 0.94) for urine samples). Conclusions: The sensitivity of self-collected vaginal samples for the detection of CIN2+ was similar to that of cervical samples and justifies consideration of this sample for primary screening.